Evaluation of the polymorphisms in the exons 2 to 4 of the TP53 in cervical carcinoma patients from a Brazilian population - Fernandes, T. A. A. M.; Lima, G. L. F.; De souza, F. C. G.; Fernandes, J. V.; Meissner, R. V. (Cellular and Molecular Biology, 2008)
The majority of TP53 polymorphisms and cervical cancer association studies have only analyzed codon 72 polymorphism. Eight polymorphisms were reported in the region encompassing exon 2 to 4 of TP53 that codify the aminoterminal p53 region containing domains involved in the transcription transactivation and apoptosis induction. We investigated if the polymorphisms present in this region were associated with cervical cancer risk. A total of 140 samples (83 from Brazilian patients with cervical carcinoma and 57 from Brazilian healthy women) were analyzed by PCR and DNA sequencing. Only three from the eight TP53 polymorphisms described in the analyzed region were polymorphic within our samples: the 11827 base from intron 2, the 16bp duplication in the intron3 and the codon 72 (Arg>Pro) from exon 4. No statistically significant association was observed between polymorphisms from intron 2 and the 16bp duplication from intron 3 with cervical cancer. No statistically significant difference in the frequency of homozygotes for Arg in relation to other genotypes was found when comparing patient and healthy groups (OR=0.70; 95% CI= 0.31-1.56; p= 0.222). However, Arg/Pro heterozygotes were more frequent within HPV positive cancer patients than in healthy women (p=0.023; OR (Arg/Pro:Pro/Pro)= 5.82; 95% CI: 1.22-30.78; p=0.024).